2020
DOI: 10.1007/s43440-020-00202-2
|View full text |Cite
|
Sign up to set email alerts
|

Update on the neurodevelopmental theory of depression: is there any ‘unconscious code’?

Abstract: Depression is currently one of the most common psychiatric disorders and the number of patients receiving antidepressant treatment is increasing every year. Therefore, it is essential to understand the underlying mechanisms that are associated with higher prevalence of depression. The main component leading to the change in functioning, in the form of apathy, anhedonia, lack of motivation and sleep disturbances, is stress. This is the factor that in recent decades—due to the civilization speed, dynamic technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 92 publications
0
29
0
1
Order By: Relevance
“…The presence of the “cytokine storm” in severe cases of COVID-19 emphasizes the significance of immunological mechanisms in the pathophysiology of this disease [ 31 , 32 ]. Mindful of the inflammation theory of depression [ 33 , 34 ], elevated pro-inflammatory cytokines might be a nexus in the shared pathology of these diseases. Fetal and early childhood exposure to viral infections enhances the risk of developing psychiatric disorders [ 35 , 36 ].…”
Section: The Neuropsychiatric Effects Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…The presence of the “cytokine storm” in severe cases of COVID-19 emphasizes the significance of immunological mechanisms in the pathophysiology of this disease [ 31 , 32 ]. Mindful of the inflammation theory of depression [ 33 , 34 ], elevated pro-inflammatory cytokines might be a nexus in the shared pathology of these diseases. Fetal and early childhood exposure to viral infections enhances the risk of developing psychiatric disorders [ 35 , 36 ].…”
Section: The Neuropsychiatric Effects Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Even if the etiopathogenesis of BD has not been clarified yet, an interaction between genetic and environmental risk factors seems highly plausible. The literature extensively demonstrated that the immune and inflammatory systems may play a crucial role in determining the onset and recurrence of major depressive disorder (MDD) [31,32]. Thus, the hypothesis of neuroinflammatory mechanisms in the etiology of BD has gained growing credibility [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it has been reported that the gene expression of IL-17, IL-21, IL-23, and IL-35 was substantially higher in patients with MDD than in controls, which suggests that the expression of specific inflammatory genes may be a factor in the etiopathogenesis of depressive disorders. Additionally, these cytokines may affect the metabolism of neurotransmitters and neuroendocrine functions in the brain and may be markers and new potential therapeutic targets for recurrent depressive disorders 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%